1997
DOI: 10.1074/jbc.272.7.4429
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Developmental Expression, and Phosphorylation of Ribosomal Protein S6 in the Endocrine Gland Responsible for Insect Molting

Abstract: Phosphorylation of ribosomal protein S6 is requisite for prothoracicotropic hormone (PTTH)-stimulated specific protein synthesis and subsequent ecdysteroidogenesis in the prothoracic glands of the tobacco hornworm, Manduca sexta. To better understand the role of S6 in regulating ecdysteroidogenesis, S6 cDNA was isolated from a Manduca prothoracic gland cDNA library and sequenced. The deduced protein is comprised of 253 amino acids, has a molecular weight of 29,038, and contains four copies of a 10-amino acid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Another effect of PTTH is the phosphorylation of ribosomal protein S6 in the PGs of Manduca (Song and Gilbert, 1997). In agreement with this report, phosphorylation of S6 was induced 2.7-fold after 1 h exposure of PGs to PTTH.…”
Section: Ribosomal Protein S6supporting
confidence: 92%
“…Another effect of PTTH is the phosphorylation of ribosomal protein S6 in the PGs of Manduca (Song and Gilbert, 1997). In agreement with this report, phosphorylation of S6 was induced 2.7-fold after 1 h exposure of PGs to PTTH.…”
Section: Ribosomal Protein S6supporting
confidence: 92%
“…Protein samples were prepared according to a protocol modified from Song and Gilbert (1997). In brief, Drosophila tissues were dissected from the indicated stages at room temperature under the Ringers' solution and homogenized on ice in phosphate-buffered saline (PBS) (136 mM NaCl, 1.1 mM K 2 HPO 4 , 2.7 mM KCl, 8.0 mM Na 2 HPO 4 , pH 7.4) using a disposable pestle in an Eppendorf tube.…”
Section: Polyacrylamide Gel Electrophoresis and Western Blot Analysismentioning
confidence: 99%
“…Previous studies indicated that PTTH-stimulated cAMP and Ca 2þ are intracellular second messengers in both Manduca sexta (Smith et al, 1984(Smith et al, , 1985Fellner et al, 2005) and Bombyx mori (Gu et al, 1996(Gu et al, , 1998. In M. sexta, it was reported that p70S6 kinase (S6K) and ribosomal protein S6 are related to PTTHstimulated ecdysteroidogenesis (Song and Gilbert, 1994, 1997. In addition, extracellular signal-regulated kinase (ERK) phosphorylation was found to be involved in PTTH's stimulation of ecdysteroidogenesis (Rybczynski et al, 2001;Lin and Gu, 2007;Gu et al, 2010).…”
Section: Introductionmentioning
confidence: 97%